2014
DOI: 10.4049/jimmunol.1301904
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms Underlying the Immediate and Transient Global Tolerization of Splenic Dendritic Cells after Vaccination with a Self-Antigen

Abstract: Dendritic cells (DC) are important orchestrators of the immune response, ensuring that immunity against pathogens is generated while immunity against healthy tissues is prevented. Using the tumor Ag MUC1, we previously showed that i.v. immunization of MUC1.Tg mice, but not WT, with a MUC1 peptide resulted in transient tolerization of all splenic DC. These DC did not upregulate costimulatory molecules and induced regulatory T cells (Treg) rather than effector T cells. They were characterized by suppressed expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Farkas et al . demonstrated that mucin 1 transgenic mice developed transient tolerization of splenic dendritic cells when intravenously immunized with a mucin 1 peptide [ 30 , 31 ]. In systemic lupus erythematosus (SLE), antigen-induced tolerance has been widely addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Farkas et al . demonstrated that mucin 1 transgenic mice developed transient tolerization of splenic dendritic cells when intravenously immunized with a mucin 1 peptide [ 30 , 31 ]. In systemic lupus erythematosus (SLE), antigen-induced tolerance has been widely addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cell maturation has been shown to be impaired upon immunization with a self-antigen in a Treg-, IL-10R-dependent manner [51, 52]. Maturation markers were restored however, in the presence of pro-inflammatory TLR3 signals [51], suggesting this type of DC tolerance could be overridden during an infection if necessary. Other TLR ligands such as CpG or co-administration of viruses and dendritic cells have helped override established T cell tolerance to tumors [53, 54].…”
Section: Introductionmentioning
confidence: 99%